THE EFFECT OF DIFFERENT RAW MATERIALS HANDLING OFCATFISH (Clarias gariepinus) ON QUALITY OF AMPLANG CRACKERS - Faradilla, Shella; Sumarto, Sumarto; Dewita, Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This study was aimed to determine the effect of different raw materials handling of catfish (Clarias gariepinus) on the quality of amplang crackers. The used method was an experimental method, with a non-factorial Completely Randomized Design (CRD) consisting of 3 levels of treatment, namely fresh minced meat (A1), frozen minced meat (A2) and frozen surimi (A3). The observed parameters were proximate expansion (water content, ash, fat, and protein), developmental power, hygroscopic and organoleptic (appearance, aroma, flavor and texture). The results showed that the A1(9) treatment was the best treatment. The characteristics were the bright colors, specific fish aroma, specific fish flavor, and crispiness and dense.Furthermore the proximate value was 2.64% moisture, 1.78% ash content, 18.36% fat content, 9.41% protein content, 232.68% linear expansion and0.96% hygroscopic. Keywords: amplang crackers, catfish, handling.